Preparation of graphite-phase carbon nitride-based composite photocatalyst and application of graphite-phase carbon nitride-based composite photocatalyst in synthesis of hydrogen peroxide
Through the graphite phase carbon nitride composite photocatalyst prepared by thermal polymerization at high temperature, the high energy consumption and safety hazards of traditional hydrogen peroxide synthesis methods are solved, and the effect of efficient hydrogen peroxide synthesis under full-band light irradiation is achieved. , and exhibit excellent adaptability and stability in an alkaline environment.
Patent Information
- Application Number
- CN202411313352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Traditional hydrogen peroxide synthesis methods consume a lot of energy, expensive equipment, complex process and pose safety hazards. In addition, the single-component graphite phase carbon nitride photocatalyst is easy to recombine photogenerated carriers and have weak light absorption capacity in photocatalysis.
The graphite phase carbon nitride composite photocatalyst is prepared by thermal polymerization of melamine and sodium tripolyphosphate at high temperature. Na-CN is obtained by calcining and washing, combined with deionized water and isopropanol as a mixed solvent, and under full-band light irradiation Perform photocatalytic reactions to achieve efficient synthesis of hydrogen peroxide.
The prepared composite photocatalyst shows good adaptability in a wide pH range, and can efficiently synthesize hydrogen peroxide in an alkaline environment. It has high yield and good stability, and does not require additional oxygen, achieving low cost and cleanliness. , safe hydrogen peroxide synthesis.
Smart Images

Figure CN119140144A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and in particular relates to the preparation of a graphite phase carbon nitride-based composite photocatalyst and its application in hydrogen peroxide synthesis. Background Art
[0002] Nowadays, with the development of modern industry, energy crisis and environmental pollution are more serious. Among them, energy shortage and environmental degradation are major problems that mankind faces and urgently needs to solve in the 21st century. Therefore, the utilization of new energy and environmental pollution control are of great significance to the national sustainable development strategy. As an environmentally friendly green chemical, hydrogen peroxide (H2O2) has an increasing market demand year by year and is widely used in environmental protection, petrochemical, electronics, food and other industries. However, the traditional method of preparing hydrogen peroxide has high energy consumption, expensive equipment, complex process, certain safety hazards in the production process, and is prone to produce harmful by-products. Therefore, it is urgent to find a low-cost, clean and safe synthetic method to prepare hydrogen peroxide.
[0003] However, there are some problems in synthesizing hydrogen peroxide using traditional methods. For example, the anthraquinone method must consume a large amount of organic matter, and the electrochemical method requires electrolytes with high salt concentrations as well as additional energy and equipment input. Photocatalysis is a more promising method. Driven by solar energy, this method can reduce oxygen through photogenerated electrons and use ubiquitous oxygen and water to synthesize hydrogen peroxide. It is a clean, green and sustainable method for synthesizing hydrogen peroxide. In addition, graphite carbon nitride (g-C3N4) has attracted widespread attention since it was applied to photocatalytic water decomposition in 2009. It is an n-type semiconductor with a band gap of about 2.7eV and can absorb photons with a wavelength of less than 460nm. Compared with traditional TiO2, it has a wider spectral absorption range, and has more preparation methods, low equipment requirements and short preparation time. In addition, g-C3N4 also has the advantages of being non-toxic, environmentally friendly and free of secondary pollution. However, as a single-component catalyst, it still has the disadvantages of easy recombination of photogenerated carriers and weak light absorption ability. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation of a graphite phase carbon nitride-based composite photocatalyst and its application in hydrogen peroxide synthesis. The composite photocatalyst prepared by the present invention has a wide light absorption range and effective carrier separation efficiency in the full band, and thus has a good photocatalytic synthesis of hydrogen peroxide rate. The preparation method of the present invention is simple, the raw material source is wide, it is safe and environmentally friendly, and the requirements for equipment are relatively low.
[0005] The preparation method of the graphite phase carbon nitride-based composite photocatalyst of the present invention is to thermally polymerize melamine and sodium tripolyphosphate at high temperature, comprising the following steps: Melamine and sodium tripolyphosphate are ground in a mortar, mixed evenly and then transferred to a boat-shaped ceramic crucible, placed in a tubular furnace, and slowly heated to 450-560°C in a N2 atmosphere and calcined for 1-3 hours; after the calcination is completed, the obtained solid product is ground into powder, washed with deionized water and ethanol several times, and finally dried at 60°C overnight to obtain Na-CN(N2).
[0006] The mass ratio of melamine to sodium tripolyphosphate is 3:1-3, the calcination temperature is 450-560°C, and the insulation time is 1-3h.
[0007] Furthermore, the mass ratio of melamine to sodium tripolyphosphate is 3:2.
[0008] Furthermore, the calcination temperature was 520 °C, the heating rate was 5 °C / min, and the holding time was 2 h.
[0009] The invention discloses an application of the graphite phase carbon nitride-based composite photocatalyst in the synthesis of hydrogen peroxide.
[0010] The specific steps are as follows: deionized water and isopropanol are used as a mixed solvent, a graphite phase carbon nitride-based composite photocatalyst is added, and the mixture is evenly dispersed. Then, the mixed solution is transferred to a photocatalytic reactor, stirred under light-proof and sealed conditions, and no additional oxygen is introduced. The reaction is carried out under the irradiation of a xenon lamp light source (light intensity is 120 mW / cm 2 , wavelength is full band), to obtain hydrogen peroxide.
[0011] Furthermore, the preferred catalyst mass to solvent volume ratio is 1:1250 (g / mL); in addition, the xenon lamp is a full-band irradiation.
[0012] In the mixed solvent, the volume ratio of deionized water to isopropanol is 9:1.
[0013] The pH value of the catalytic reaction system is 3-10, preferably 7-10.
[0014] The beneficial effects of the present invention are as follows: The best catalyst prepared by the present invention shows good adaptability in a wide pH range, and the hydrogen peroxide photocatalytically synthesized in an alkaline environment is better than that in an acidic environment, and the yield of hydrogen peroxide does not change much in the range of pH 3-10. In addition, the best catalyst synthesized can efficiently synthesize hydrogen peroxide under alkaline conditions.
[0015] The present invention adopts a simple calcination method to prepare a graphite phase carbon nitride-based composite photocatalyst, which can realize the efficient synthesis of H2O2 through photocatalytic reaction under full-band conditions without oxygen exposure (light intensity of 120 mW / cm 2, wavelength is full band, catalyst dosage is 0.8 g / L, reaction system is to add 45 mL deionized water and 5 mL isopropanol in a 100 mL beaker, no additional oxygen is introduced), reaction time is 3 h, and the yield reaches 12.3 mmol / L. Through the effective regulation of the composite photocatalyst synthesis process and the test of photocatalytic H2O2 production performance, the optimal ratio of each component in the catalytic material is obtained.
[0016] The material prepared by the present invention is prepared by thermal polymerization of melamine and sodium tripolyphosphate at high temperature. The method is simple, the operation process is simple, and it is easy to expand and can be prepared on a large scale. It is used as a photocatalyst in the process of photocatalytic production of hydrogen peroxide, and has high photocatalytic activity and good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 X-ray powder diffraction spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air).
[0018] Figure 2 Scanning electron micrographs of CN (a), Na-CN1.0 (N2) (b) and Na-CN1.0 (Air) (c).
[0019] Figure 3 Transmission electron micrographs of CN (a), Na-CN1.0 (N2) (b) and Na-CN1.0 (Air) (c).
[0020] Figure 4 UV-visible diffuse reflectance images of CN, Na-CN1.0(N2) and Na-CN1.0(Air).
[0021] Figure 5 Electrochemical impedance diagrams of CN, Na-CN1.0(N2) and Na-CN1.0(Air).
[0022] Figure 6 Photoluminescence spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air).
[0023] Figure 7 Fourier infrared spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air).
[0024] Figure 8 This is the hydrogen peroxide synthesis rate diagram of Na-CN1.0(N2) in the full band at different calcination temperatures.
[0025] Fig. 9 This is the hydrogen peroxide synthesis rate diagram of Na-CN1.0(N2) in the full band under different insulation times.
[0026] Fig.10 This is a graph of hydrogen peroxide synthesis rate under different ratios of catalysts in the full band.
[0027] Fig.11 This is the synthesis rate diagram of hydrogen peroxide of CN, Na-CN1.0(N2) and Na-CN1.0(Air) in the full band.
[0028] Fig.12 This is the synthesis rate diagram of hydrogen peroxide of CN, Na-CN1.0(N2) and Na-CN1.0(Air) under visible light and full wavelength band.
[0029] Fig.13 This is the synthesis rate diagram of Na-CN1.0(N2) and hydrogen peroxide at different pH.
[0030] Fig.14 The pH value of Na-CN1.0(N2) suspension with different concentrations of NaOH added (initially pH=8). DETAILED DESCRIPTION
[0031] In order to make the technical purpose, technical solution and beneficial effects of the present invention clearer, the technical solution of the present invention is further described below in conjunction with specific examples, but the protection scope of the present invention is not limited thereto. Example 1: Preparation of CN
[0032] Grind 1.5 g of melamine in a mortar for 20 minutes, transfer to a boat-shaped ceramic crucible after mixing evenly, put it into a tube furnace, and heat it to 520°C at a heating rate of 5°C / min in a N2 atmosphere, and keep it warm for 2 hours; after the reaction is completed, transfer the calcined material to a mortar and grind it into powder, transfer it to a 250 mL beaker, add 100 mL of water and stir for 5 hours. After the reaction is completed, centrifuge, take the precipitate, wash it repeatedly with water several times, and finally put the solid precipitate in a 60°C oven and dry it for 24 hours to obtain CN.
[0033] Example 2: Preparation of Na-CN1.0(N2) 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were put into a mortar and ground for 20 minutes. After mixing evenly, they were transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was raised to 520°C at a heating rate of 5°C / min and kept warm for 2 hours. After the reaction was completed, the calcined material was further transferred to a mortar and ground into powder, transferred to a 250 mL beaker, and stirred for 5 hours with 100 mL of water. After the reaction was completed, centrifuged, the precipitate was taken, and it was repeatedly washed with water for several times. Finally, the solid precipitate was placed in a 60°C oven and dried for 24 hours to obtain Na-CN1.0(N2).
[0034] Example 3: Preparation of Na-CN1.0(N2)-X 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were put into a mortar and ground for 20 minutes. After mixing evenly, they were transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was raised to 450°C, 480°C, 520°C and 560°C at a heating rate of 5°C / min, and kept warm for 2 h. After the reaction was completed, the calcined material was further transferred to a mortar and ground into powder, transferred to a 250 mL beaker, and stirred for 5 h with 100 mL of water. After the reaction was completed, centrifuged, the precipitate was taken, and it was repeatedly washed with water for several times. Finally, the solid precipitate was placed in a 60°C oven and dried for 24 h to obtain Na-CN1.0(N2)-X. X represents different temperatures.
[0035] Example 4: Preparation of Na-CN1.0(N2)-Y 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were put into a mortar and ground for 20 minutes. After mixing evenly, they were transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was raised to 520°C at a heating rate of 5°C / min, and the temperature was kept for 1h, 2h and 3h respectively. After the reaction was completed, the calcined material was further transferred to a mortar and ground into powder, transferred to a 250 mL beaker, and stirred for 5h with 100 mL of water. After the reaction was completed, centrifuged, the precipitate was taken, and it was repeatedly washed with water for several times. Finally, the solid precipitate was placed in a 60°C oven and dried for 24h to obtain Na-CN1.0(N2)-Y. Y represents different times.
[0036] Example 5: Preparation of Na-CN (N2)-Z 1.5 g of melamine and Z g of sodium tripolyphosphate were put into a mortar and ground for 20 minutes. After mixing evenly, they were transferred to a boat-shaped ceramic crucible and placed in a tube furnace. Under a N2 atmosphere, the temperature was raised to 520°C at a heating rate of 5°C / min and kept warm for 2 h. After the reaction was completed, the calcined material was further transferred to a mortar and ground into powder, transferred to a 250 mL beaker, and stirred for 5 h with 100 mL of water. After the reaction was completed, centrifuged, the precipitate was taken, and washed repeatedly with water. Finally, the solid precipitate was placed in a 60°C oven and dried for 24 h to obtain Na-CN(N2)-Z. Z represents the mass of sodium tripolyphosphate. Example 6: Preparation of Na-CN1.0 (Air)
[0037] 1.5 g of melamine and 1.0 g of sodium tripolyphosphate were put into a mortar and ground for 20 minutes. After mixing evenly, they were transferred to a crucible and placed in a muffle furnace and heated to 520°C for 2 h. After the reaction was completed, the calcined material was further transferred to a mortar and ground into powder, transferred to a 250 mL beaker, and stirred for 5 h after adding 100 mL of water. After the reaction was completed, the mixture was centrifuged, the precipitate was taken, and it was repeatedly washed with water for several times. Finally, the solid precipitate was placed in a 60°C oven and dried for 24 h to obtain Na-CN1.0(Air). Performance Test:
[0038] Figure 1 The X-ray powder diffraction spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air) photocatalysts. The results show that pure g-C3N4 shows different diffraction peaks at 13.1° and 27.7°, which are respectively attributed to the (100) crystal plane and (002) crystal plane of graphite carbon nitride, and are respectively attributed to the interlayer order of tri-s-triazine units and the interlayer stacking of conjugated aromatics. For the modified Na-CN1.0(N2) and Na-CN1.0(Air) samples, the main phase structure of graphite carbon nitride changes. It can be seen from the figure that both samples show diffraction peaks of sodium metaphosphate, which may be generated by the high-temperature decomposition of sodium tripolyphosphate.
[0039] Figure 2 The scanning electron microscope images of CN (a), Na-CN1.0 (N2) (b) and Na-CN1.0 (Air) (c) show that CN is seriously agglomerated, with an irregular block structure and a rough and uneven surface. Na-CN1.0 (Air) presents a long rod-like structure, while Na-CN1.0 (N2) shows a more obvious three-dimensional structure, which is formed by a series of irregular protruding rice-like structures arranged in an interlaced manner.
[0040] Figure 3 Transmission electron micrographs of CN (a), Na-CN1.0 (N2) (b) and Na-CN1.0 (Air) (c). It can be seen that CN has an irregular block structure and uneven distribution and is easy to stack. Na-CN1.0 (Air) presents a rectangular stacking structure, while Na-CN1.0 (N2) presents a thinner layered stacking structure.
[0041] Figure 4The UV-visible diffuse reflectance graphs of CN, Na-CN1.0(N2) and Na-CN1.0(Air) are shown in Figure 1. As can be seen from the figure, compared with CN and Na-CN1.0(Air), the maximum absorption edge of Na-CN1.0(N2) undergoes significant absorption and red shift of the absorption edge, and the light absorption range of the catalyst is significantly broadened. In addition, the absorption of the Na-CN1.0(N2) sample in the 480-900 nm region is also slightly improved, which can be attributed to the n–π* transition of the lone pair of electrons at the –C≡N defect position. The enhanced adsorption capacity improves the utilization rate of photogenerated carriers and improves the photocatalytic performance.
[0042] Figure 5 The electrochemical impedance diagrams of CN, Na-CN1.0(N2) and Na-CN1.0(Air) are shown in the figure. It can be seen that the curvature radius of CN and Na-CN1.0(Air) is smaller than that of Na-CN1.0(N2), indicating that the impedance values of CN and Na-CN1.0(Air) are also smaller than those of Na-CN1.0(N2). This means that Na-CN1.0(N2) has better conductivity, indicating that the catalyst has better charge migration and separation capabilities.
[0043] Figure 6 The photoluminescence spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air) are shown in Figure 2. The PL signal intensity gradually decreases from Na-CN1.0(Air) to Na-CN1.0(N2), indicating that the increase in the content of -C≡N groups can effectively promote the separation of electrons and holes. This is because the -C≡N group has the property of accepting electrons and can absorb photogenerated electrons, which is beneficial to the separation and transmission of photogenerated electron-hole pairs.
[0044] Figure 7 The Fourier transform infrared spectra of CN, Na-CN1.0(N2) and Na-CN1.0(Air) are shown in Figure 1. -1 , 1150-1800 cm -1 and 3000-3400 cm -1 There are typical characteristic peaks between 810cm -1 The sharp characteristic peaks are attributed to the out-of-plane bending characteristic peaks of the carbon nitrogen triazine ring structure unique to carbon nitride, 1150-1800 cm -1 The peak widths between the two are the CN stretching vibrations of the NC=N carbon nitrogen heterocycle, ranging from 3000 cm -1 and 3400 cm -1 The broad characteristic peaks between the two are attributed to the stretching vibration of NH. In addition, the peak at 2165 cm -1The signal of the cyano group (-C≡N) converted from the terminal -C-NH2 is stronger for Na-CN1.0(N2), and the presence of more cyano groups may help to enhance the visible light absorption, charge separation and transfer to improve the photocatalytic performance. In addition, due to the incorporation of phosphate, the -1 The OP signal was observed at 1071 cm -1 The corresponding infrared peak is the PN bond.
[0045] Figure 8 This is the full-band hydrogen peroxide synthesis rate diagram of Na-CN1.0(N2) at different calcination temperatures. The holding time is 2 h. It can be seen from the figure that the synthesis performance of hydrogen peroxide shows a trend of first increasing and then decreasing with the increase of calcination temperature, and the best effect is achieved at a calcination temperature of 520°C.
[0046] Fig. 9 The figure shows the hydrogen peroxide synthesis rate of Na-CN1.0 (N2) at different holding times in the full band, and the calcination temperature is 520 ° C. It can be seen from the figure that the synthesis performance of hydrogen peroxide also shows a trend of first increasing and then decreasing with the extension of the holding time, and the best effect is achieved when the holding time is 2 h.
[0047] The synthesis performance of hydrogen peroxide in the full band was investigated under the optimal calcination temperature and the optimal holding time. Fig.10 As shown in the figure, it can be seen that when melamine is fixed at 1.5 g, with the addition of sodium tripolyphosphate, the performance of photocatalytic synthesis of hydrogen peroxide shows a trend of first increasing and then decreasing. When the mass of sodium tripolyphosphate added is 1 g, the performance of photocatalytic synthesis of hydrogen peroxide reaches the best.
[0048] Fig.11 The photocatalytic effect of CN, Na-CN1.0(N2) and Na-CN1.0(Air) in the photocatalytic production of hydrogen peroxide (with a xenon lamp as the light source and a light intensity of 120 mW / cm 2 , the wavelength is full band, the amount of catalyst is 40 mg, the reaction system is to add 45 mL of deionized water and 5 mL of isopropanol in a 100 mL beaker, and no additional oxygen is introduced). It can be seen from the figure that the concentration of hydrogen peroxide in the solution of Na-CN1.0(N2) reaches 12.3 mmol / L after 3 hours of reaction, while the concentration of hydrogen peroxide in the solution of CN and Na-CN1.0(Air) can only reach 1.6 mmol / L and 5.3 mmol / L after 3 hours of reaction. The hydrogen peroxide production rate of Na-CN1.0(N2) is significantly higher than that of CN and Na-CN1.0(Air), indicating that it has the best photocatalytic performance in producing hydrogen peroxide.
[0049] Fig.12This is a comparison of the synthesis rates of hydrogen peroxide of CN, Na-CN1.0 (N2) and Na-CN1.0 (Air) under visible light and full-band. From the figure, we can see that the synthesis rate of hydrogen peroxide of the catalyst under the full-band is much higher than that under visible light. It can also be seen here that ultraviolet light plays an important role in the production of hydrogen peroxide by the catalyst.
[0050] In addition, in order to highlight the advantages of the catalyst prepared by the present invention, the synthesis rate of hydrogen peroxide of Na-CN1.0 (N2) at different pH values was tested. Fig.13 It can be seen that, unlike other reports in which the efficiency of the catalyst in synthesizing H2O2 in an alkaline environment is inhibited, Na-CN1.0(N2) shows good adaptability in a wide pH range, and the production of H2O2 does not change much in the pH range of 3-10. In addition, Na-CN1.0(N2) can efficiently synthesize hydrogen peroxide in a wide pH range.
[0051] The proton donor capacity was assessed by increasing the pH of the suspension by adding sodium hydroxide (NaOH) to monitor the consumption of protons. Fig.14 As shown, when 2.5 and 10 mM NaOH were added, the pH value of the NaCN1.0(N2) suspension increased between 0.6 and 0.9, indicating that NaCN1.0(N2) has excellent proton donor ability, which is one of the reasons why NaCN1.0(N2) can excellently synthesize H2O2 in an alkaline environment.
[0052] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a graphite phase carbon nitride-based composite photocatalyst, Features The steps include: Melamine and sodium tripolyphosphate were ground in a mortar, mixed evenly, and then transferred to a boat-shaped ceramic crucible and placed in a tube furnace for calcination. After the calcination was completed, the obtained solid product was ground into powder, washed with deionized water and ethanol, and dried to obtain Na-CN(N 2 ).
2. The preparation method according to claim 1, Features: The calcination process was carried out in a nitrogen atmosphere.
3. The preparation method according to claim 2, Features: The calcination temperature is 450-560°C and the holding time is 1-3h.
4. The preparation method according to claim 3, Features: The calcination temperature was 520 °C and the holding time was 2 h.
5. The preparation method according to claim 1, Features: The mass ratio of melamine to sodium tripolyphosphate is 3:1-3.
6. The preparation method according to claim 5, Features: The mass ratio of melamine to sodium tripolyphosphate is 3:
2.
7. Use of the graphite phase carbon nitride-based composite photocatalyst prepared by the preparation method according to any one of claims 1 to 6 in the synthesis of hydrogen peroxide.
8. The use according to claim 7, Features: Deionized water and isopropanol are used as a mixed solvent, a graphite phase carbon nitride-based composite photocatalyst is added and dispersed evenly, and then the mixed solution is transferred to a photocatalytic reactor, stirred under light-proof and sealed conditions without additional oxygen, and reacted under irradiation of a xenon lamp light source to obtain hydrogen peroxide.
9. The use according to claim 8, Features: The irradiation wavelength covers the entire wavelength range.
10. The use according to claim 8, Features: The pH value of the catalytic reaction system is 3-10.
Citation Information
Patent Citations
Sodium doped graphite phase carbon nitride prepared by one-step synthesis and application thereof
CN106582765A
Catalyst for synthesis of hydrogen peroxide by catalyzing oxygen reduction under visible light and preparation method thereof
CN109012728A
Photocatalysis catalyst, and preparation method and application thereof
CN112958130A
Multiphase nano composite photocatalyst as well as preparation method and application thereof
CN116408127A
Preparation method of energy-saving modified carbon nitride, modified carbon nitride and application
CN118287121A
Cited By
Homojunction photocatalyst as well as preparation method and application thereof
CN120205210A
